Impact of probiotic supplementation on exercise endurance among nonelite athletes: a randomized, placebo-controlled, double-blind, clinical trial - McDermott, C. A.; Judkins, T. C.; Vincent, H. K.; Culpepper, T.; Colee, J.; Nieves Jr., C.; Mathews, A. E.; Langkamp-Henken, B. (Applied Physiology, Nutrition, and Metabolism, 2024)
This randomized, placebo-controlled, double-blind, parallel trial investigated whether generally healthy adult, nonelite runners would have a greater time-to-exhaustion during submaximal treadmill running with probiotic versus placebo supplementation. It was hypothesized that the probiotic would impact training progression by reducing gastrointestinal (GI) and cold/flu symptoms. Participants who typically ran =24 km/week, ran or cross-trained 3-5 days per week, and had a maximal oxygen intake (VO2 max) in the 60-85th percentile were enrolled. V?O2 max was used to establish individualized workload settings (85% of VO2 max) for the submaximal endurance tests at baseline and following 6 weeks of supplementation with a probiotic (Lactobacillus helveticus Lafti L10, 5×109 CFU/capsule/day) or placebo. Participants self-reported GI and cold/flu symptoms and physical activity via daily and weekly questionnaires. Outcomes were tested using a linear model to determine if mean response values adjusted for baseline differed between groups. Twenty-eight participants (n = 14/group), aged 25 ± 5 years (mean ± SD) with a body mass index of 23 ± 3 kg/m2, completed the study. At the final visit the probiotic group had a lower time-to-exhaustion versus the placebo group (P = 0.01) due to an increase in time-to-exhaustion with the placebo (1344 ± 188 to 1565 ± 219 s, P = 0.01) with no change with the probiotic (1655 ± 230 to 1547 ± 215 s, P = 0.23). During the intervention, the probiotic group completed fewer aerobic training sessions per week (P = 0.02) and trained at a lower intensity (P = 0.007) versus the placebo group. Few GI and cold/flu symptoms were reported with no differences between groups. Time-to-exhaustion increased in the placebo group, possibly due to differences in training habits.